Tipe dan Gaya Kepemimpinan dalam Perspektif Pendidikan Islam - Agung Fahri; Bayo Hadomuan Tanjung; Robial; Fitri Angguan; Nirva Diana (Attractive : Innovative Education Journal, 2024)
This article discusses the types and styles of leadership in the perspective of Islamic education. Leadership style which is a characteristic of a leader in carrying out the management activity process. As well as the type of leadership that generally describes the general character of leadership in the world and Indonesia. The study in this research is a literature review that relies on data sources in the form of books/scriptures, scientific articles in journals, research results, and print media opinions related to the discussion theme, namely Types and Styles in the Perspective of Islamic Education. The data obtained from various sources are then processed and analyzed objectively and in depth through review activities, grouping, systematization, interpretation and verification of data from reading results from various sources. The results of this study conclude that there are four types of leadership in general, namely autocratic (authoritarian) leadership, democratic leadership, Laissez-Faire leadership and transformational leadership. The author also concludes regarding the Leadership Style that we usually encounter, namely charismatic style, servant style, coaching, and visionary. According to Islam, Management and leadership methods in the field of Islam prioritize justice and can be concluded from an Islamic perspective, namely justice, exemplary, trustworthy, and deliberation.